2022
DOI: 10.2147/itt.s284988
|View full text |Cite
|
Sign up to set email alerts
|

Immune Checkpoint Blockade for the Treatment of Hodgkin Lymphoma

Abstract: Classical Hodgkin lymphoma is biologically different than other lymphomas. The cancer cells only occupy a small amount of the lymph node and evade the immune system by amplification of PD-L1 and PD-L2. Therefore, checkpoint inhibitors are a logical treatment option for Hodgkin lymphoma patients to unlock the immune system. Checkpoint inhibitors have shown high response rates in clinical trials in advanced-stage Hodgkin lymphoma. The two most commonly used checkpoint inhibitors are pembrolizumab and nivolumab, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Following great successes in solid tumors such as non-small cell lung cancer, melanoma, renal cell carcinoma [66] , and squamous cell carcinoma of the head and neck [67] , interest has risen to explore these inhibitors in hematologic malignancies. Notably, patients with relapsed or refractory HL showed promising outcomes to PD-1 inhibitors probably due to the PD-L1 and PD-L2 up-regulation in >95% of cases during the immune escape [68] . While ICIs are a logical treatment option for HL patients, there are controversial results about their efficacies in NHL ones.…”
Section: Discussionmentioning
confidence: 99%
“…Following great successes in solid tumors such as non-small cell lung cancer, melanoma, renal cell carcinoma [66] , and squamous cell carcinoma of the head and neck [67] , interest has risen to explore these inhibitors in hematologic malignancies. Notably, patients with relapsed or refractory HL showed promising outcomes to PD-1 inhibitors probably due to the PD-L1 and PD-L2 up-regulation in >95% of cases during the immune escape [68] . While ICIs are a logical treatment option for HL patients, there are controversial results about their efficacies in NHL ones.…”
Section: Discussionmentioning
confidence: 99%
“…It is the first FDA-approved ICI in relapsed HL as a third-line drug. Growing evidence supports its administration as a second or first-line drug in newly diagnosed HL [ 15 ]. In a recent retrospective study, nivolumab showed comparable safety and efficacy in treating patients with refractory HL [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the distinct biology of cHL is inspiring the development of newer molecular therapies [ 152 ]. RS cells exhibit genetic amplification of the 9p24.1 locus; further analysis revealed their overexpression of programmed death ligand 1 (PD-L1) and programmed death ligand 2 [ 152 , 153 ]. This discovery led to the rational development of PD-1 checkpoint inhibitors.…”
Section: Novel Therapies For R/r Hlmentioning
confidence: 99%